HIV/AIDS Awareness and the Level of Sexual Risk Behaviors Among Senior High School Students: An Evaluation - Baron, Jomarie (Journal of Social, Humanity, and Education, 2022)
Purpose: The study primarily aimed to assess the level of Senior High School students’ awareness of HIV/AIDS and their sexual risk behaviors in the division of General Santos City and to find out if there is a significant relationship between the two variables. Research methodology: The research combines qualitative and quantitative methods to explore different phenomena in every aspect of this timely and relevant social issue today- HIV and AIDS. The statistical measure used to test the hypothesis were the Average Percentage, Mean, Z- test, and Pearson Product-moment Correlation. Results: Findings revealed that awareness of HIV/ AIDS was Fair for both male and female students. Although their level of sexual risk behaviors was Very Low, still it posed a great threat to spreading the virus, especially to male students who are likely to indulge in risky sexual activities compared to female students. Limitations: This study was limited to the five (5) mega public secondary schools in the division of General Santos City. Variables under investigation were delimited, for awareness of HIV/AIDS focuses only on the transmission myth, attitude, and facts. On the other hand, the sexual risk behaviors variables revolved only around the influence of social media, peer influence, the influence of video content materials, non-self-protection efficacy, and influence of substance use. Contribution: The study will expose the present condition of the youth’s sexual risk behaviors and their awareness of HIV/AIDS which will be the basis for program implementation and policies to contain the spread of the virus.